Blackout risk prevention in a smart grid based flexible optimal strategy using Grey Wolf-pattern search algorithms. (1st July 2015) - Mahdad, Belkacem; Srairi, K.
Graphical abstract: Highlights: A generalized optimal security power system planning strategy for blackout risk prevention is proposed. A Grey Wolf Optimizer dynamically coordinated with Pattern Search algorithm is proposed. A useful optimized database dynamically generated considering margin loading stability under severe faults. The robustness and feasibility of the proposed strategy is validated in the standard IEEE 30 Bus system. The proposed planning strategy will be useful for power system protection coordination and control. Abstract: Developing a flexible and reliable power system planning strategy under critical situations is of great importance to experts and industrials to minimize the probability of blackouts occurrence. This paper introduces the first stage of this practical strategy by the application of Grey Wolf Optimizer coordinated with pattern search algorithm for solving the security smart grid power system management under critical situations. The main objective of this proposed planning strategy is to prevent the practical power system against blackout due to the apparition of faults in generating units or important transmission lines. At the first stage the system is pushed to its margin stability limit, the critical loads shedding are selected using voltage stability index. In the second stage the generator control variables, the reactive power of shunt and dynamic compensators are adjusted in coordination with minimization the active and reactive power at critical loads to maintain the system at security state to ensure service continuity. The feasibility and efficiency of the proposed strategy is applied to IEEE 30-Bus test system. Results are promising and prove the practical efficiency of the proposed strategy to ensure system security under critical situations.